RIPK3/Fas-Associated Death Domain Axis Regulates Pulmonary Immunopathology to Cryptococcal Infection Independent of Necroptosis - Fa, Zhenzong; Xie, Qun; Fang, Wei; Zhang, Haibing; Zhang, Haiwei; Xu, Jintao; Pan, Weihua; Xu, Jinhua; Olszewski, Michal A.; Deng, Xiaoming; Liao, Wanqing (Frontiers in Immunology, 2017)
Fas-associated death domain (FADD) and receptor-interacting serine/threonine kinase 3 (RIPK3) are multifunctional regulators of cell death and immune response. Using a mouse model of cryptococcal infection, the roles of FADD and RIPK3 in anti-cryptococcal defense were investigated. Deletion of RIPK3 alone led to increased inflammatory cytokine production in the C. neoformans-infected lungs, but in combination with FADD deletion it led to a robust Th1-biased responses with M1-biased macrophage activation. Rather than being protective, these responses led to paradoxical C. neoformans expansion and rapid clinical deterioration in Ripk3-/- and Ripk3-/-Fadd-/- mice. The increased mortality of Ripk3-/- and even more accelerated mortality in Ripk3-/-Fadd-/- mice was attributed to profound pulmonary damage due to neutrophil-dominant infiltration with prominent up-regulation of pro-inflammatory cytokines. This phenomenon was partially associated with selective alterations in the apoptotic frequency of some leukocyte subsets, such as eosinophils and neutrophils, in infected Ripk3-/-Fadd-/- mice. In conclusion, our study shows that RIPK3 in concert with FADD serve as physiological “brakes”, preventing the development of excessive inflammation and Th1 bias, which in turn contributes to pulmonary damage and defective fungal clearance. This novel link between the protective effect of FADD and RIPK3 in antifungal defense and sustenance of immune homeostasis may be important for the development of novel immunomodulatory therapies against invasive fungal infections.